Ersatz model tests. (18th July 2017) - Jarvis, S.; Sharpe, J.; Smith, A. D.
Abstract: This paper describes how statistical methods can be tested on computer-generated data from known models. We explore bias and percentile tests in detail, illustrating these with examples based on insurance claims and financial time series.